STRATEGI SATUAN POLISI PAMONG PRAJA DALAM PENATAAN, PENGAWASAN, DAN PENERTIBAN PEDAGANG KAKI LIMA DI KOTA METRO - Simarmata, Theresia Helen (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2023)
The Civil Service Police Unit or commonly abbreviated as Satpol PP is an organization that has the task and function and authority in organizing the enforcement of regional regulations and regional decisions. Satpol PP in handling street vendors changed the old pattern with a new one, namely using persuasive and humanist approach strategies. The purpose of this study is to find out how the strategy carried out in structuring, supervising and regulating street vendors (PKL) by Satpol PP with a persuasive and humanist approach method. The method used in this study is descriptive qualitative, with the location of the study at the Metro City Civil Service Police Unit office and Pasar Cendrawasi. Informants in research use purposive sampling techniques, data collection techniques with triangulation techniques and in research data collection techniques with observation, interviews and literature studies. The results of this study stated that in structuring, supervising and regulating street vendors carried out by Satpol PP using a persuative and humanist approach model is good enough, the community can change the image of Satpol PP for the better and solve problems by dialogue. The obstacles faced when implementing peruasive and humanist methods such as lack of public awareness, insufficient availability of human resources such as employees at Satpol PP Kota Metro and dense activities carried out by regional officials both formal and informal cause coordination to be less than optimal. Keywords : Strategy; Unit; Police; Pamong; Praja.